2022
DOI: 10.3389/fviro.2022.894531
|View full text |Cite
|
Sign up to set email alerts
|

Omicron Spike Protein Has a Positive Electrostatic Surface That Promotes ACE2 Recognition and Antibody Escape

Abstract: High transmissibility is a hallmark of the Omicron variant of SARS-CoV-2. Understanding the molecular determinants of Omicron’s transmissibility will impact development of intervention strategies. Here we map the electrostatic potential surface of the Spike protein to show that major SARS-CoV-2 variants have accumulated positive charges in solvent-exposed regions of the Spike protein, especially its ACE2-binding interface. Significantly, the Omicron Spike-ACE2 complex has complementary electrostatic surfaces. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
50
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 38 publications
12
50
0
4
Order By: Relevance
“…Indeed, according to the experiments [ 51 , 52 ], the escaping mutations for the studied ultrapotent antibodies can emerge in the charged positions K444 and R493 of the S-RBD Omicron, causing a modest ~5–7-fold decrease in neutralization, attributed to only partially optimized electrostatic contacts. Consistent with the related studies [ 109 , 110 , 111 , 112 ], our analysis similarly indicated that potent antibodies against S-RBD Omicron should be enriched with negatively charged residues in positions interacting with the Omicron positively charged mutational sites. At the same time, a far more significant increase was seen in the number of hydrophobic contacts in the S-RBD and S-RBD Omicron complexes with the synergistic antibody pairs ( Table 2 ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Indeed, according to the experiments [ 51 , 52 ], the escaping mutations for the studied ultrapotent antibodies can emerge in the charged positions K444 and R493 of the S-RBD Omicron, causing a modest ~5–7-fold decrease in neutralization, attributed to only partially optimized electrostatic contacts. Consistent with the related studies [ 109 , 110 , 111 , 112 ], our analysis similarly indicated that potent antibodies against S-RBD Omicron should be enriched with negatively charged residues in positions interacting with the Omicron positively charged mutational sites. At the same time, a far more significant increase was seen in the number of hydrophobic contacts in the S-RBD and S-RBD Omicron complexes with the synergistic antibody pairs ( Table 2 ).…”
Section: Resultssupporting
confidence: 91%
“…Our analysis supports the notion that the electrostatic interactions could play an important stabilizing role in the S-RBD complexes with ultrapotent antibodies [ 109 , 110 ]. Recent quantitative assessment of the antibody escape showed that the S-RBD Omicron variant can be resistant to most neutralizing antibodies, primarily due to either unfavorable or only partly optimized electrostatic interactions [ 111 , 112 ]. Indeed, according to the experiments [ 51 , 52 ], the escaping mutations for the studied ultrapotent antibodies can emerge in the charged positions K444 and R493 of the S-RBD Omicron, causing a modest ~5–7-fold decrease in neutralization, attributed to only partially optimized electrostatic contacts.…”
Section: Resultsmentioning
confidence: 99%
“…35 Similar results and analysis at pH 7 are found in the recent paper by Gan and colleagues using the Poisson-Boltzmann approach (except for BA.4 and BA.5 which were not included in their study). 62 The order of the computed isoelectric points (pI) is wt, Alpha (8.6) < Beta, Gamma (8.9) < Delta, Omicron, BA.2, BA.2.12.1, BA. from calculations using the ab initio fragment molecular orbital method (<Z (RBDwt) >=+2 and <Z (ACE2) >=-24).…”
Section: Physical Chemistry Properties Of the Proteinsmentioning
confidence: 99%
“…23 Other results that became available after this comparison also report the same trends. 61,62 For the recent variants from the Omicron family, no data is yet available at the moment of writing this work.…”
Section: Free Energy Of Interactions At Phmentioning
confidence: 99%
See 1 more Smart Citation